Highly efficient thiomolybdate [Mo2S12]2- nanocluster cocatalyst decorated on TiO2 to boost photocatalytic hydrogen evolution. (26th May 2022) - Zhang, Rongguo; Gong, Kewei; Du, Fuying; Cao, Shunan
Abstract: The exploitation of noble-metal-free photocatalysts with high solar-to-H2 conversion efficiency is a hot topic in the photocatalysis field. Molybdenum sulfide materials, which have good physicochemical properties and excellent hydrogen evolution activity, have become an effective noble metal cocatalyst substitute and attracted widespread attention. In this work, a highly efficient photocatalyst constructed by decorating thiomolybdate [Mo2 S12 ] 2- nanoclusters on TiO2 is reported for the first time. The resultant [Mo2 S12 ] 2- /TiO2 photocatalyst shows a remarkable enhanced hydrogen evolution rate under the Xenon light irradiation. At the optimal loading amount of [Mo2 S12 ] 2-, the photocatalyst exhibits a photocatalytic hydrogen evolution rate of 213.1 μmol h −1 g −1, which is about 51 times that of the pure TiO2 . Characterization results show that the intimate contact between [Mo2 S12 ] 2- and TiO2 promotes the separation of hole-electron pairs, prolongs the lifetime of carriers, and thereby increases the photocatalytic activity. Furthermore, abundant bridging S in the [Mo2 S12 ] 2- acts as active sites for hydrogen evolution, which also contributes to the enhanced hydrogen production rate. This work demonstrates an efficient way for the construction of noble-metal-free hydrogen evolution photocatalyst and provides a useful reference for the development of low cost photocatalysts in the future. Graphical abstract: Image 1 Highlights: [Mo2 S12 ] 2- was decorated on TiO2 to obtain the [Mo2 S12 ] 2- /TiO2 nanocomposite by a facile impregnation method. The [Mo2 S12 ] 2- /TiO2 shows a greatly enhanced hydrogen evolution activity. The [Mo2 S12 ] 2- cluster acts as the active site for hydrogen evolution. The decoration of [Mo2 S12 ] 2- on TiO2 promotes the separation of hole-electron pairs and prolongs the lifetime of carriers.